An analysis of sources of financing public and non-public higher education in Poland in 2004–2009 - Ćwiąkała-Małys, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The main aim of the article is the presentation of sources of financing public and non-public higher education in Poland. The detailed structure of revenues with dynamics of changes of their particular items for both kinds of schools is demonstrated. Moreover, the role of the governmental budget and a self-governmental budget in financing higher education system in Poland is shown. The research spans the period of six years i.e. 2004-2009. The article presents the revenue structure of Polish higher education according to the changes of rules of financing higher education proposed by Ministry of Science and Higher Education
Keywords: publiczne szkolnictwo wyższe; niepubliczne szkolnictwo wyższe; przychody z działalności dydaktycznej; przychody z działalności badawczej